The living presidency : an originalist argument against its ever-expanding powers - Prakash, Saikrishna Bangalore (The Belknap Press of Harvard University Press, 2020)
"Beloved by liberals, the living Constitution evolves with the times. But one downside has been the erosion of constitutional constraints on executive action. Saikrishna Prakash argues that if we want to rein in this imperial, living presidency, we must embrace constitutional originalism and revive the framers' vision of the separation of powers"--